Creating inclusive materials: a university Service-Learning experience - Belen Suárez-Lantarón; Gloria Solís-Galán (Firenze University Press, 2023)
This paper presents a service-learning experience at the University of Extremadura (Spain). Its objective has been to develop an educational experience using service-learning in which students acquire curricular learning, adapting awareness-raising materials and evaluating the importance of providing, also, a quality inclusive educational response to individual needs. A total of 75 university students participated in the experience. An observation record, a report preparation and a satisfaction questionnaire are used as a method for evaluation. The results obtained are presented in relation to three issues: (a) the project, finding a positive evaluation by the students of participation, collaboration, interest and involvement; (b) learning, noting that the qualification has improved in terms of curricular learning, but also in relation to soft skills; and (c) the service, promoting awareness values among the educational community towards inclusion and sustainability. In conclusion, it is highlighted that the use of this type of methodology favours the motivation and involvement of students in the development of their learning, not only in relation to academic issues but also commitment and social responsibility.   Creare materiali inclusivi: un'esperienza universitaria di Service-Learning. L'obiettivo di questa esperienza è stato quello di sviluppare un'esperienza educativa utilizzando l'apprendimento di servizio in cui gli studenti acquisiscono l'apprendimento curriculare, adattando materiali di sensibilizzazione e valutando l'importanza di fornire una risposta educativa inclusiva di qualità anche ai bisogni individuali. All'esperienza hanno partecipato complessivamente 75 studenti universitari. Come metodo di valutazione vengono utilizzati strumenti qualitativi (registrazione delle osservazioni e redazione del rapporto) e strumenti quantitativi (questionario di soddisfazione). I risultati ottenuti sono presentati in relazione a tre temi: (a) il progetto, riscontrando una valutazione positiva da parte degli studenti di partecipazione, collaborazione, interesse e coinvolgimento; (b) l'apprendimento, osservando che la qualifica è migliorata in termini di apprendimento curriculare, ma anche in relazione alle competenze trasversali; e (c) il servizio, promuovendo valori di consapevolezza tra la comunità educativa verso l'inclusione e la sostenibilità. In conclusione, si evidenzia che l'uso di questo tipo di metodologia favorisce la motivazione e il coinvolgimento degli studenti nello sviluppo del loro apprendimento, non solo in relazione alle questioni accademiche ma anche all'impegno e alla responsabilità sociale.